Titin‐cap associates with, and regulates secretion of, Myostatin - G. Nicholas; Mark Thomas; Brett Langley; W. Gregory Somers; Ketan Patel; C. Fred Kemp; Mridula Sharma; Ravi Kambadur (2002)
Abstract Myostatin, a secreted growth factor, is a key negative regulator of skeletal muscle growth. To identify modifiers of Myostatin function, we screened for Myostatin interacting proteins. Using a yeast two‐hybrid screen, we identified Titin‐cap (T‐cap) protein as interacting with Myostatin. T‐cap is a sarcomeric protein that binds to the N‐terminal domain of Titin and is a substrate of the titin kinase. Mammalian two‐hybrid studies, in vitro binding assays and protein truncations in the yeast two‐hybrid system verified the specific interaction between processed mature Myostatin and full‐length T‐cap. Analysis of protein–protein interaction using surface plasmon resonance (Biacore, Uppsala, Sweden) kinetics revealed a high affinity between Myostatin and T‐cap with a KD of 40 nM. When T‐cap was stably overexpressed in C 2 C 12 myoblasts, the rate of cell proliferation was significantly increased. Western analyses showed that production and processing of Myostatin were not altered in cells overexpressing T‐cap, but an increase in the retention of mature Myostatin indicated that T‐cap may block Myostatin secretion. Bioassay for Myostatin confirmed that conditioned media from myoblasts overexpressing T‐cap contained lower levels of Myostatin. Given that Myostatin negatively regulates myoblast proliferation, the increase in proliferation observed in myoblasts overexpressing T‐cap could thus be due to reduced Myostatin secretion. These results suggest that T‐cap, by interacting with Myostatin, controls Myostatin secretion in myogenic precursor cells without affecting the processing step of precursor Myostatin. J. Cell. Physiol. 193: 120–131, 2002. © 2002 Wiley‐Liss, Inc.